Analisis Pengaruh Variabel Mikro Dan Makro Ekonomi Terhadap VaR Bank Umum Syariah Di Indonesia - Eko Hariyadi; Akhsyim Afandi (Jurnal Ilmiah Ekonomi Islam, 2021)
Profit-sharing as the main product of Islamic banks has a higher level of risk than other contracts, resulting in a low mudharabah financing portfolio. This study is intended to determine the effect of micro and macroeconomic variables on the Value at Risk of Islamic commercial banks in Indonesia. Value at Risk is proxied by the potential loss of profit-sharing financing on the Mudharabah and Musyarakah investment portfolios of Islamic commercial banks whose data is obtained from OJK Sharia Banking Statistics. Monthly time series data, covering June 2014 to December 2020 are selected. The test equipment used in this study used the ARDL (Autoregressive Distributed Lag) test. Based on the results of data analysis, the Value at Risk variable proxy is influenced by the CAR, EXC, NPF, and ROA variables. Meanwhile, the variables of GDP, INF, and FDR do not affect VaR. High CAR and NPF increase the VaR of Islamic commercial banks. Meanwhile, the decline in ROA and depreciation of the rupiah reduced the VaR of Islamic commercial banks.